High yield strength 6111 series aluminum alloy, automobile seat slide rail and preparation method thereof
By controlling the proportions of Cu, Er, and Yb elements and a specific process flow, and utilizing the comprehensive strengthening factor Φ=[Cu/(Er+Yb)]×(Er/Yb)^0.5, the problem of balancing high strength and high plasticity as well as material texture in 6111 series aluminum alloy slide rails was solved, achieving the preparation of aluminum alloy slide rails with high yield strength, excellent plasticity, and no material texture.
Patent Information
- Application Number
- CN202610931371.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-06-26
AI Technical Summary
Existing 6111 series aluminum alloys are difficult to balance in terms of high strength and high plasticity, and are prone to material marks after anodizing. Traditional methods of adjusting elements are not effective, resulting in difficulties in formula selection and unstable results.
By controlling the proportions of Cu, Er, and Yb elements and employing a comprehensive strengthening factor Φ=[Cu/(Er+Yb)]×(Er/Yb)^0.5, combined with a specific process flow, a synergistic improvement in strength, plasticity, and resistance to grain marks is achieved, resulting in the preparation of aluminum alloy slide rails with high yield strength.
It achieves a yield strength of ≥350MPa, elongation of ≥10%, peel force of ≥50KN for aluminum alloy slide rails, and no material marks after anodizing, solving the problem of balancing high strength and high plasticity, and simplifying the industrial production process.
Smart Images

Figure CN122446018B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of non-ferrous metal composite materials technology, and more specifically, it relates to a high yield strength 6111 series aluminum alloy, an automotive seat slide rail, and a method for preparing the same. Background Technology
[0002] With the trend of lightweighting in automobiles, aluminum alloy slide rails, as the core component of seat adjustment parts, have extremely high requirements for the comprehensive performance of materials: they need high strength to ensure collision safety and load-bearing capacity, high plasticity to meet the requirements of complex cross-section forming, and excellent surface quality to avoid directional stripes (material marks) after anodizing. Among them, 6111 series aluminum alloys have become the mainstream material for manufacturing slide rails due to their good formability and aging strengthening potential.
[0003] However, the 6111 series aluminum alloys in related technologies have long faced a core contradiction: it is difficult to balance high strength and high plasticity, and the surface texture problem is difficult to eliminate. In order to pursue strength, existing related technologies tend to increase the Cu content, but this will lead to a sharp drop in elongation and increase the material's sensitivity to processing technology, making it easy to produce texture after subsequent anodizing.
[0004] On the other hand, in order to improve plasticity and resistance to grain texture, the industry has tried to add rare earth elements such as Er and Yb. It is known that Er and Yb can form Al3RE dispersed phase with Al, which has the effect of pinning grain boundaries and refining grains. However, this is essentially a "trial and error" approach. The effects of Cu, Er and Yb on strength, plasticity and resistance to grain texture are often mutually restrictive or even contradictory. It is not easy to predict and control the performance by adjusting a single element.
[0005] Therefore, when facing the multi-objective problem of "high strength, high plasticity, and no material texture", it is necessary to spend months or even years to conduct a large number of formula screenings, and the results often result in one aspect being neglected. Based on this, this application provides a high yield strength 6111 series aluminum alloy, an automotive seat slide rail and its preparation method. Summary of the Invention
[0006] To solve the above technical problems, a high yield strength 6111 series aluminum alloy, an automotive seat slide rail and its preparation method are provided. The aim is to achieve a synergistic improvement in strength, plasticity and anti-gravel performance by constraining the element relationship and dosage, so that the finished slide rail has a yield strength ≥350MPa, elongation ≥10%, peel force ≥50KN and no visible grain marks on the surface after anodizing.
[0007] In a first aspect, this application provides a high yield strength 6111 series aluminum alloy, composed of the following components by weight percentage:
[0008] Si: 0.70-0.74 wt.%;
[0009] Fe: ≤0.12 wt.%;
[0010] Cu: 0.66-1.07 wt.%;
[0011] Mn: 0.16-0.20 wt.%;
[0012] Mg: 0.90-0.94 wt.%;
[0013] Cr: 0.07-0.09 wt.%;
[0014] Er: 0.08-0.12 wt.%;
[0015] Yb: 0.05-0.08 wt.%;
[0016] Sr: 0.017-0.023 wt.%;
[0017] Ti: 0.010-0.020 wt.%;
[0018] The balance consists of Al and unavoidable impurities;
[0019] The above components must simultaneously satisfy the following equation constraint for the overall strengthening factor Φ:
[0020] .
[0021] Preferably, it consists of the following components by weight percentage:
[0022] Si: 0.72±0.02 wt.%;
[0023] Fe: ≤0.12 wt.%;
[0024] Cu: 0.70±0.02 wt.%;
[0025] Mn: 0.18±0.02 wt.%;
[0026] Mg: 0.92±0.02 wt.%;
[0027] Cr: 0.08±0.01 wt.%;
[0028] Er: 0.10±0.005 wt.%;
[0029] Yb: 0.065±0.005 wt.%;
[0030] Sr: 0.020±0.003 wt.%;
[0031] Ti: 0.015±0.005 wt.%.
[0032] By adopting the above technical solution, under the constraints of precise component selection and mandatory equations, an excellent balance of strength, plasticity, and resistance to chipping is effectively achieved. This solution is not a simple formulaic induction, but rather an unexpected discovery based on previous theoretical exploration and experiments. The reasons for this are analyzed as follows:
[0033] 1) This application first tried the traditional single-factor test method and found that increasing Cu can increase strength but the elongation drops sharply and the material texture becomes severe;
[0034] Adding Er or Yb alone can improve elongation and resistance to graining, but the strength loss is significant.
[0035] After further attempts at binary and ternary combinations, most formulas still could not meet the requirements simultaneously. Only a few "lucky" formulas achieved excellent results with yield strength >350MPa, elongation >10%, and no material marks.
[0036] 2) In-depth analysis of these high-performance formulations revealed that their Cu content is concentrated between 0.68-0.72%, Er between 0.09-0.11%, and Yb between 0.06-0.07%.
[0037] When these values were substituted into the tentative relation Cu / (Er+Yb), the calculated values fell between 4.0 and 4.5. Further attempts to add Er / Yb corrections revealed that when square root corrections were used, the calculated values of these superior formulations were highly concentrated in a narrow range of 5.2 to 5.4.
[0038] After further verification of more than 20 sets of formulas, the inventors finally concluded that: almost all formulas that meet the Φ=5.0-8.0 standard can stably achieve the target performance; while formulas with Φ values outside this range will always have one or more performance characteristics that fail to meet the standard.
[0039] 3) In addition, different exponents k (i.e. Φ=[Cu / (Er+Yb)]×(Er / Yb)^k) were tried. It was found that the Φ value had the best performance discrimination only when k=0.5. Other exponents (such as k=1 or k=0.2) all had varying degrees of misjudgment. This further confirms that the Φ formula and its exponent in this invention are not simple mathematical choices, but specific technical means based on the inversion of a large amount of experimental data.
[0040] 4) The physical meaning of Φ is clear: the larger the Φ value, the more Cu there is and the higher the Er / Yb ratio, the more dominant the Q phase reinforcement, and the more likely it is to have high strength; the smaller the Φ value, the more rare earth there is and the higher the Yb ratio, the more dominant the Al3(Er,Yb) dispersed phase, and the more likely it is to have high plasticity and resistance to material texture. It can be seen that Φ is the key balance window to achieve the target performance.
[0041] Secondly, this application provides an automotive seat slide rail, which is made from the high yield strength 6111 series aluminum alloy described in any of the above through melting and casting, homogenization, hot rolling, cold rolling, solution treatment, aging and forming processing. The specifications of the slide rail are as follows: length 760-765mm, width 78-82mm, height 41-45mm, thickness 4-6mm, and overall straightness (including torsion) ≤0.4mm.
[0042] Thirdly, this application provides a method for manufacturing an automotive seat slide rail, using the aluminum alloy casting rod described in any of the above claims as raw material, comprising the following steps:
[0043] S1. Melting and casting: After batching, melting, refining, degassing and grain refinement of any of the above aluminum alloy formulas, the alloy is poured into ingots.
[0044] S2, Homogenization Annealing: The ingot obtained in S1 is subjected to a two-stage homogenization annealing process.
[0045] S3. Hot rolling: The ingot obtained from S2 is reheated and then hot rolled in multiple passes, and then water-quenched immediately after the final rolling.
[0046] S4, Cold rolling: Cold rolling the hot-rolled plate obtained from S3, and annealing it in the middle when cold rolling to the intermediate thickness;
[0047] S5. Solution treatment: The cold-rolled sheet obtained in S4 is solution treated and then quenched.
[0048] S6. Two-stage aging treatment: The board obtained from S5 is subjected to two-stage aging treatment in sequence;
[0049] S7. Straightening and Anodizing: The sheet material obtained in S6 is subjected to tension straightening, cutting, and anodizing to obtain the car seat slide rail.
[0050] Preferably, the specific conditions for homogenization annealing in S2 are as follows:
[0051] First stage: Heat to 460±5℃ at a rate of ≤100℃ / h, and hold for 2±0.5h;
[0052] Second stage: Heat to 565±5℃ at a rate of ≤50℃ / h and hold for 8±1h;
[0053] The furnace was then cooled to below 200°C, and then air-cooled to room temperature.
[0054] Preferably, the specific conditions for hot rolling in S3 are: initial rolling temperature of 520±10℃, final rolling temperature ≥320℃, total hot rolling reduction ≥85%, and water quenching to room temperature within 5 seconds after final rolling.
[0055] Preferably, the specific conditions for cold rolling in S4 are as follows:
[0056] When the thickness is cold rolled to 2.8±0.1mm, intermediate annealing is carried out at 430±5℃ for 2±0.5h. The total cold rolling processing rate is ≥60%, and the final thickness is 1.5±0.02mm.
[0057] Preferably, the specific conditions for the solution treatment in S5 are: holding at 555±2℃ for 15±2 minutes, and then transferring to water at 20±1℃ for quenching within 3 seconds;
[0058] The specific conditions for the two-stage aging treatment described in S6 are as follows: the first-stage aging is carried out in an oil bath at 80±1℃ for 8±0.5 hours, and the second-stage aging is carried out in an air-circulating furnace at 170±2℃ for 5±0.5 hours, followed by forced air cooling to room temperature.
[0059] By adopting the above technical solutions, the integrated process of melting and casting, homogenization, hot rolling, cold rolling, solution treatment, two-stage aging, straightening and anodizing achieves deep synergy between the process and the specific alloy composition, thereby effectively leveraging the design effect of the aforementioned comprehensive strengthening factor Φ.
[0060] In particular, by combining two-stage heating homogenization with compositional design, immediate water quenching after hot rolling, rapid transfer after solution treatment, and two-stage aging, the optimal combination of alloying elements within the Φ value window is ensured, maximizing the synergistic strengthening and pinning effect of the Q phase and the Al3(Er,Yb) phase.
[0061] In summary, this application has the following beneficial effects:
[0062] 1) Through extensive preliminary exploratory experiments, this application unexpectedly discovered and summarized the intrinsic quantitative relationship between Cu, Er, Yb and the target performance, namely the comprehensive enhancement factor Φ. This discovery went through a complete process of "single element failure, binary / ternary combination disorder, unexpected discovery of excellent points, data backfitting, Φ proposal, index screening, and experimental verification", and has extremely high reference and application value.
[0063] 2) By forcing the alloy composition to meet the constraint formula of Φ, it is possible to stably achieve excellent comprehensive performance with yield strength ≥350MPa, elongation ≥10%, peel force ≥50KN and no material marks. Moreover, there is a significant critical effect of Φ value: below 5.0, strength failure occurs, and above 8.0, plasticity and surface quality failure occur. The index k=0.5 is the optimal value selected through a large number of experiments.
[0064] 3) This application simplifies the complex multi-objective alloy design problem into a quantifiable and predictable single factor Φ control problem, providing a clear technical path for the stable industrial production of high-strength, high-plasticity, anti-fracture aluminum alloys, and breaking through the traditional formula development path that relies on the "trial and error method".
[0065] Furthermore, compared to existing Er / Yb-containing aluminum alloy technologies, this application overcomes the shortcomings of traditional aluminum alloys that cannot meet the comprehensive indicators for slide rails by using the "Cu-Er-Yb" ternary quantitative synergy and the forced constraint of the Φ factor, achieving a unity of "high strength, high plasticity, high peel resistance, and high surface quality". Attached Figure Description
[0066] Figure 1 This is a front view of the car seat slide rail in Example 1;
[0067] Figure 2 This is a side view of the car seat slide rail in Example 1;
[0068] Figure 3 This is a top view of the car seat slide rail in Example 1. Detailed Implementation
[0069] The following is in conjunction with the embodiments and appendices Figure 1-3 This application will be described in further detail.
[0070] Performance testing
[0071] First, the car seat slide rails from each embodiment and comparative example were selected as test samples. Then, their room temperature tensile properties, peel strength, and texture evaluation were tested respectively. The specific test conditions and steps are as follows:
[0072] 1. Room temperature tensile properties: According to GB / T 228.1-2010 "Metallic materials - Tensile testing - Part 1: Test method at room temperature", standard tensile specimens are cut from the slide rail along the processing direction and tested by the testing machine to obtain tensile strength (Rm), yield strength (Rp0.2) and elongation after fracture (A);
[0073] 2. Peel force test: Assemble the car seat slide rail with the matching slider, perform a peel test on a universal testing machine, and record the maximum peel force (KN);
[0074] 3. Material texture evaluation: After the car seat slide rail is treated with the aforementioned anodizing process, the surface is visually observed at a distance of 40cm under a D65 standard light source. If no defects are visible to the naked eye, it can be evaluated as "no material texture". If material texture is visible to the naked eye, it can be judged as "slight material texture" or "obvious material texture" according to the amount of material texture.
[0075] Five samples were tested in each group of the above experiments, and the average value was recorded.
[0076] Before finalizing the proposed solution, the inventors conducted extensive exploratory experiments to reveal the intrinsic quantitative relationship between the contents of Cu, Er, and Yb and yield strength, elongation, and grain texture.
[0077] The following are representative examples from the preliminary research, and they are analyzed and compared layer by layer according to the logic of "single element addition, binary combination, and ternary synergy". The specific conditions are as follows:
[0078] The basic fixed composition (excluding Cu, Er, and Yb) is: Si 0.72%, Fe 0.10%, Mn 0.18%, Mg 0.92%, Cr 0.08%, Sr 0.020%, Ti 0.015%, with the balance being Al.
[0079] The manufacturing process of automotive seat slide rails is as follows:
[0080] S1. Smelting and casting: Prepare the ingredients according to the formula in Table 1, and bake all raw materials at 150℃ for 2 hours;
[0081] The crucible is preheated to 600℃, and the loading order is pure aluminum ingot, industrial silicon, and covering agent. The temperature is raised to 740±5℃ to melt, and then Al-Mn and Al-Cr master alloys are added in sequence.
[0082] Al-Er, Al-Yb, and Al-Sr were pressed into the bell jar;
[0083] Add cathode copper;
[0084] Ar gas refining for 15 minutes, standing for 10 minutes, then skimming off the residue;
[0085] Pure magnesium ingots were pressed into a bell jar;
[0086] Cool down to 700±5℃ and feed in Al-Ti-B fibers;
[0087] Poured at 695±5℃ into a mold preheated to 200℃, then cooled by water mist;
[0088] S2. Homogenization annealing: Heat to 460℃ at 100℃ / h and hold for 2h, then heat to 565℃ at 50℃ / h and hold for 8h, then furnace cool (≤30℃ / h) to 200℃, and finally air cool to room temperature;
[0089] S3. Hot rolling: The ingot is reheated to 520℃ and held for 1 hour. It is then hot rolled in 9 passes on a two-roll hot rolling mill. The final rolling temperature is 335℃. After the final rolling, it is immediately sprayed with water to quench to room temperature.
[0090] S4. Cold rolling: The 4.5mm hot-rolled plate is cold-rolled. When it is cold-rolled to 2.8mm, it is subjected to intermediate annealing at 430℃ for 2 hours (air furnace, air cooling), and then cold-rolled to 1.5mm.
[0091] S5. Solution treatment: Hold the 1.5mm cold-rolled plate in a 555℃ salt bath furnace for 15 minutes, then transfer it to a 20℃ water bath for quenching within 3 seconds and hold for 2 minutes.
[0092] S6. Two-stage aging treatment: First, keep it in an oil bath at 80℃ for 8 hours, then transfer it to an air circulation furnace at 170℃ for 5 hours, and finally force it to cool to room temperature.
[0093] S7. Straightening and Anodizing: Perform tension straightening with an elongation of 0.8%, and cut according to the drawings;
[0094] Then, the following steps were performed sequentially: degreasing at 60℃ with 5% NaOH for 2 minutes, alkaline etching at 55℃ with 10% NaOH for 3 minutes, neutralization at room temperature with 15% HNO3 + 2% HF for 1 minute, anodizing at 18℃ with 15% H2SO4 and 1.2 A / dm² for 30 minutes, and sealing with deionized water at 95℃ for 20 minutes.
[0095] I. Limitations of Single Elements and Binary Combinations
[0096] First, we tried adjusting Cu, Er, or Yb individually, as well as the Cu+Er binary combination, and the results are as follows:
[0097]
[0098] Based on the table above, C1 shows that increasing the Cu content can achieve higher strength, but the elongation drops sharply and the surface texture becomes severe. C2 and C3 indicate that adding Er or Yb alone can significantly improve plasticity and surface quality, but the strength loss is obvious (yield ≤ 325 MPa). C4 further shows that even when Cu and Er are combined, strength and plasticity cannot be achieved simultaneously. Therefore, it can be seen that neither single-element nor binary combination can meet the comprehensive goal of "yield ≥ 350 MPa, elongation ≥ 10%, and no surface texture".
[0099] II. Unexpected discovery of ternary synergy and induction of the Φ factor
[0100] Subsequently, attempts were made to conduct multi-level formulations in the Cu, Er, and Yb ternary system. It was found that most formulations still could not meet the standards at the same time, but a few "lucky" formulations unexpectedly performed well.
[0101] The following are three typical formulations:
[0102]
[0103] As can be seen from C5 and C6, even if Cu, Er and Yb are contained at the same time, if the Er / Yb ratio is seriously unbalanced, the strength or plasticity will still not meet the standards. However, after analyzing the unexpectedly discovered excellent formula C7, it was found that its Cu content is concentrated in 0.68-0.72%, Er in 0.09-0.11%, and Yb in 0.06-0.07%.
[0104] Therefore, we further attempted to construct the functional relationship between Cu, Er, and Yb, and found that when the expression Φ = [Cu / (Er+Yb)]×(Er / Yb) was used... 0.5 At that time, the Φ value of P1 was approximately 5.26. Subsequently, more than 20 formulations were verified and it was found that formulations that met the Φ=5.0-8.0 standard could almost always stably achieve the target performance; while formulations with Φ values outside this range always had one or more performance characteristics that did not meet the standard.
[0105] III. Screening and Verification of the Exponent k
[0106] To confirm the unique validity of the exponent 0.5 in the above expression, the inventors of this application also tried three exponents, k=0.2, 0.5, and 1.0, and compared their accuracy in identifying qualified formulas.
[0107] Typical formulations containing elements near the boundary were selected for testing, as follows:
[0108]
[0109] The data in the table shows that when k=1, the Φ=5.79 of P3 falls into the 5-8 range, but the actual strength does not meet the standard, which will cause misjudgment; when k=0.2, the Φ=7.81 of P2 falls into the 5-8 range, but the actual elongation does not meet the standard, which will also cause misjudgment.
[0110] Only when k=0.5, the Φ values of all qualified formulations (P1, P4) are within the range of 5-8, while the Φ values of all unqualified formulations (P2, P3, P5) fall outside this window, resulting in the highest discrimination accuracy. This confirms that the index k=0.5 is the optimal value obtained by backfitting based on a large amount of experimental data.
[0111] Based on the above preliminary research experiments, the following conclusions can be drawn:
[0112] 1) Single-element or binary combinations cannot simultaneously achieve high strength, high plasticity and no texture.
[0113] 2) There is a nonlinear cooperative relationship among Cu, Er, and Yb, and the condition Φ = [Cu / (Er+Yb)] ×(Er / Yb) must be satisfied. ^0.5 ∈ [5.0,8.0].
[0114] 3) Φ has a significant critical effect: below 5.0, the strength is insufficient, and above 8.0, the plasticity and surface quality deteriorate. The index k=0.5 is the only optimal value selected by experiments, and other indices all have varying degrees of misjudgment.
[0115] The effectiveness of the Φ window is further verified below in conjunction with Examples 1-5 and Comparative Examples 1-5.
[0116] Examples 1-5
[0117] A car seat slide rail has a length of 763mm, a width of 79.6mm, a height of 43mm, a thickness of 5mm, and an overall straightness (including torsion) of ≤0.4mm. Specifically... Figure 1-3 As shown;
[0118] The composition of the alloying elements and their corresponding weight percentages in the processed casting rod are shown in Table 1 below, and the rod was prepared through the following steps:
[0119] S1. Smelting and casting: Prepare the ingredients according to the formula in Table 1, and bake all raw materials at 150℃ for 2 hours;
[0120] The crucible is preheated to 600℃, and the loading order is pure aluminum ingot, industrial silicon, and covering agent. The temperature is raised to 740±5℃ to melt, and then Al-Mn and Al-Cr master alloys are added in sequence.
[0121] Al-Er, Al-Yb, and Al-Sr were pressed into the bell jar;
[0122] Add cathode copper;
[0123] Ar gas refining for 15 minutes, standing for 10 minutes, then skimming off the residue;
[0124] Pure magnesium ingots were pressed into a bell jar;
[0125] Cool down to 700±5℃ and feed in Al-Ti-B fibers;
[0126] Poured at 695±5℃ into a mold preheated to 200℃, then cooled by water mist;
[0127] S2. Homogenization annealing: Heat to 460℃ at 100℃ / h and hold for 2h, then heat to 565℃ at 50℃ / h and hold for 8h, then furnace cool (≤30℃ / h) to 200℃, and finally air cool to room temperature;
[0128] S3. Hot rolling: The ingot is reheated to 520℃ and held for 1 hour. It is then hot rolled in 9 passes on a two-roll hot rolling mill. The final rolling temperature is 335℃. After the final rolling, it is immediately sprayed with water to quench to room temperature.
[0129] S4. Cold rolling: The 4.5mm hot-rolled plate is cold-rolled. When it is cold-rolled to 2.8mm, it is subjected to intermediate annealing at 430℃ for 2 hours (air furnace, air cooling), and then cold-rolled to 1.5mm.
[0130] S5. Solution treatment: Hold the 1.5mm cold-rolled plate in a 555℃ salt bath furnace for 15 minutes, then transfer it to a 20℃ water bath for quenching within 3 seconds and hold for 2 minutes.
[0131] S6. Two-stage aging treatment: First, keep it in an oil bath at 80℃ for 8 hours, then transfer it to an air circulation furnace at 170℃ for 5 hours, and finally force it to cool to room temperature.
[0132] S7. Straightening and Anodizing: Perform tension straightening with an elongation of 0.8%, and cut according to the drawings;
[0133] Then, the following steps were performed sequentially: degreasing at 60℃ with 5% NaOH for 2 minutes, alkaline etching at 55℃ with 10% NaOH for 3 minutes, neutralization at room temperature with 15% HNO3 + 2% HF for 1 minute, anodizing at 18℃ with 15% H2SO4 and 1.2 A / dm² for 30 minutes, and sealing with deionized water at 95℃ for 20 minutes.
[0134] Table 1: Components, weight percentages, and Φ values in Examples 1-5
[0135]
[0136] Comparative Examples 1-5
[0137] An automotive seat slide rail differs from Embodiment 1 in that only the components and their corresponding weight percentages are different, as shown in the table below:
[0138] Table 2: Components, weight percentages, and Φ values in Comparative Examples 1-5
[0139]
[0140] The car seat slide rails in Examples 1-5 and Comparative Examples 1-5 were extracted and tested according to the steps and standards in the above performance test. Their room temperature tensile properties, peel force and texture evaluation were tested respectively. The average value of the test results was recorded in the table below.
[0141] Table: Performance test results of Examples 1-5 and Comparative Examples 1-5
[0142]
[0143] As can be clearly seen from the table above, the automotive seat slide rails prepared in Examples 1-5 all achieve superior overall performance compared to Comparative Examples 1-5. A detailed analysis follows:
[0144] 1) Room temperature tensile properties:
[0145] The tensile strength of Examples 1-3 reached 418-432 MPa, the yield strength was 372-389 MPa, and the elongation was 11.9-13.5%, which fully met the target of yield strength ≥350 MPa and elongation ≥10%.
[0146] Although Examples 4-5 are similar in composition, their yield strength has dropped to 342MPa and 335MPa, and their elongation has dropped to 9.8% and 9.2%, respectively, because Φ is not between 5 and 8, which fails to meet the standards.
[0147] As for Comparative Examples 1, 4, and 5, their yield strengths are all below 335 MPa. Although Comparative Examples 2 and 3 barely meet the yield standard, their elongation is only 8.2% and 9.0%, respectively, and their peel strength is also insufficient. It can be seen that only when the comprehensive strengthening factor Φ is controlled within the range of 5.0-8.0 can high strength and high plasticity be obtained at the same time.
[0148] 2) Evaluation dimensions of peel strength and texture:
[0149] Examples 1-3 exhibited peel strengths as high as 52.1-58.2 KN, and no material marks were observed after anodizing. In contrast, Examples 4-5 showed peel strengths of only 46.3 KN and 44.8 KN, respectively, and exhibited slight to obvious material marks.
[0150] The peel force of Comparative Examples 1-5 was all below 50KN (the highest being only 49.0KN). In addition to the slight texture of Comparative Examples 1, 4, and 5, the texture of Comparative Examples 2-3 was obvious. This indicates that when the Φ value deviates from the 5.0-8.0 window, not only is the strength and plasticity damaged, but the peel resistance and surface quality also deteriorate simultaneously.
[0151] Furthermore, by comparing the performance differences between the various embodiments and the comparative examples, the following conclusions can be drawn:
[0152] 1) The comprehensive enhancement factor Φ = 5.0-8.0 is the core constraint for the implementation of the scheme.
[0153] Examples 1 (Φ=5.26), 2 (Φ=6.27), and 3 (Φ=8.0) all meet the following requirements: yield strength ≥372MPa, elongation ≥11.9%, peel force ≥52.1KN, and no material marks.
[0154] However, Examples 4 (Φ=4.51) and 5 (Φ=4.13) are below the lower limit of the comprehensive strengthening factor, and their yield strength and elongation are reduced to varying degrees.
[0155] Comparative Example 2 (Φ=9.75) and Comparative Example 3 (Φ=8.66) exceeded the upper limit. Although the yield strength barely met the standard, the elongation was ≤9.0%, the peel strength was <50KN, and the material texture was obvious.
[0156] Comparative examples 1, 4, and 5 (Φ=2.80~3.76) are far below the lower limit, with yield strength <330MPa. It is evident that Φ has a significant critical effect: below 5.0, strength and peel force are insufficient; above 8.0, plasticity and surface quality deteriorate. Only when Φ is strictly controlled between 5.0 and 8.0 can the comprehensive indicators be achieved.
[0157] 2) Peel strength and grain texture are more sensitive to Φ than conventional mechanical properties.
[0158] Comparing Example 3 (Φ=8.00) and Comparative Example 3 (Φ=8.66), the yield strengths of the two are similar, but the elongation, peel force and grain pattern are significantly different, indicating that the boundary effect of the Φ window is primarily reflected in plasticity and peel resistance.
[0159] Similarly, the yield strength of Example 4 (Φ=4.51) differed from that of Comparative Example 4 (Φ=3.76) by only 17 MPa, but the peel strength differed by 4.2 KN, and the texture changed from slight to slight. Therefore, in industrial applications, Φ should be controlled within a narrow window of 5.5-7.5 to ensure sufficient safety margin.
[0160] In summary, this application has successfully achieved a synergistic unity of high strength, high plasticity, high peel resistance and no grain lines by constraining the comprehensive strengthening factor Φ through a mandatory equation. Only when Φ meets the requirement of 5.0-8.0 can the optimal ratio of Q phase and Al3(Er,Yb) dispersed phase be formed in the alloy, thereby stabilizing the yield strength at ≥372MPa, elongation ≥11.9%, peel force ≥52KN and eliminating grain lines.
[0161] It should also be noted that, due to limitations in experimental costs, patent priority time limits, and the general understanding of parameter response patterns by those skilled in the art, this specification only uses Examples 1-3 as representatives for detailed experimental verification, and does not conduct repeatable experiments on all possible combinations within the Φ window.
[0162] However, based on the physical meaning of the Φ factor, the synergistic mechanism of each element, and common knowledge in the field, which have been fully disclosed in this specification, those skilled in the art can reasonably expect without objection that excellent results can be obtained within the range of Φ=5.0-8.0 as defined in this application.
[0163] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high yield strength 6111 series aluminum alloy, characterized in that, The raw material consists of the following components by weight percentage: Si: 0.70-0.74 wt.%; Fe: ≤0.12 wt.%; Cu: 0.66-1.07 wt.%; Mn: 0.16-0.20 wt.%; Mg: 0.90-0.94 wt.%; Cr: 0.07-0.09 wt.%; Er: 0.08-0.12 wt.%; Yb: 0.05-0.08 wt.%; Sr: 0.017-0.023 wt.%; Ti: 0.010-0.020 wt.%; The balance consists of Al and unavoidable impurities; The above components must simultaneously satisfy the following equation constraint for the overall strengthening factor Φ: ; And it is prepared through the following steps: S1. Melting and casting: After batching, melting, refining, degassing and grain refinement according to the above aluminum alloy formula, the alloy is poured into ingots. S2, Homogenization Annealing: The ingot obtained in S1 is subjected to a two-stage homogenization annealing process. The specific conditions for homogenization annealing are as follows: First stage: Heat to 460±5℃ at a rate of ≤100℃ / h, and hold for 2±0.5h; Second stage: Heat to 565±5℃ at a rate of ≤50℃ / h and hold for 8±1h; The furnace was then cooled to below 200°C, and then air-cooled to room temperature. S3. Hot rolling: The ingot obtained from S2 is reheated and then hot rolled in multiple passes, and then water-quenched immediately after the final rolling. S4, Cold rolling: Cold rolling the hot-rolled plate obtained from S3, and annealing it in the middle when cold rolling to the intermediate thickness; S5. Solution treatment: The cold-rolled sheet obtained in S4 is solution treated and then quenched. The specific conditions for the solution treatment described in S5 are: holding at 555±2℃ for 15±2 minutes, and then quenching in water at 20±1℃ within 3 seconds; S6. Two-stage aging treatment: The board obtained from S5 is subjected to two-stage aging treatment in sequence; The specific conditions for the two-stage aging treatment described in S6 are as follows: the first-stage aging is carried out in an oil bath at 80±1℃ for 8±0.5 hours, and the second-stage aging is carried out in an air-circulating furnace at 170±2℃ for 5±0.5 hours, followed by forced air cooling to room temperature; S7. Straightening and Anodizing: The sheet material obtained in S6 is subjected to tension straightening, cutting, and anodizing to obtain aluminum alloy processed profiles.
2. The high yield strength 6111 series aluminum alloy according to claim 1, characterized in that, The raw materials consist of the following components by weight percentage composition: Si: 0.72±0.02 wt.%; Fe: ≤0.12 wt.%; Cu: 0.70±0.02 wt.%; Mn: 0.18±0.02 wt.%; Mg: 0.92±0.02 wt.%; Cr: 0.08±0.01 wt.%; Er: 0.10±0.005 wt.%; Yb: 0.065±0.005 wt.%; Sr: 0.020±0.003 wt.%; Ti: 0.015±0.005 wt.%; The balance consists of Al and unavoidable impurities; The above components must simultaneously satisfy the following equation constraint for the overall strengthening factor Φ: 。 3. The high yield strength 6111 series aluminum alloy according to claim 1, characterized in that, The specific conditions for hot rolling described in S3 are: initial rolling temperature of 520±10℃, final rolling temperature ≥320℃, total hot rolling reduction ≥85%, and water quenching to room temperature within 5 seconds after final rolling.
4. The high yield strength 6111 series aluminum alloy according to claim 1, characterized in that, The specific conditions for cold rolling described in S4 are as follows: when the thickness is cold rolled to 2.8±0.1mm, intermediate annealing is performed at 430±5℃ for 2±0.5h, the total cold rolling rate is ≥60%, and the final thickness is 1.5±0.02mm.
5. A car seat slide rail, characterized in that, It is obtained by forming and processing the high yield strength 6111 series aluminum alloy as described in any one of claims 1-4.
Citation Information
Patent Citations
Manufacturing method for 6XXX-series aluminum alloy plate for automobile body
CN104451208A
Al-Mg-Si series aluminum alloy with high age hardening response and preparation method of Al-Mg-Si series aluminum alloy
CN116103548A
Heat-treatment-free high-strength high-toughness die-casting aluminum alloy and preparation method thereof
CN117026023A
High-strength corrosion-resistant 6000-series aluminum alloy automobile seat sliding rail and preparation method thereof
CN117385240A
